Development of Self-Health Care Model for Pre-Retirement Teachers - Wongchan, Waraphan; Wattanaburanon, Aimutcha; Somprayoon, Suchart (Scholar: Human Sciences, 2015)
This study aimed at developing and determining the effects of self-health care model for pre-retirement teachers. The study sample consisted of teachers aged 45 to 59 years old in Bangkok Metropolis who were teaching at Nipat Wittaya School as an experiment group and Amnuaysilpa Thonburi School as a control group. The sample was recruited by means of multistage random sampling. The instruments used to collect data included the health status record form, the weekly activity assessment form, the satisfaction with activity assessment form, and the self-health care assessment form. As for data analysis, scores from the health status record form and the self-health care assessment form were analyzed in terms of mean, standard deviation, t-test and Repeated Measure ANOVA. Finally, LSD was also employed to test the differences of mean scores between each pair, with the statistical significance level set at .05. The study findings were as follows: 1. The development of self-health care model for pre-retirement teachers consisted of three main activities namely food, exercise, and rest each of which was further divided into items totaling 12 activities for teachers in the experiment group. Content validity was determined, and the IOC was equal to 0.71, hence confirming that the model was effective and could be applied for use. 2. The experiment revealed that the self-health care model for pre-retirement teachers; 1) The mean scores of health status of the experimental group before and after the experiment showed no statistical significances at the .05 level, with the mean scores of health status of the experiment group tended to improve a little bit; 2) The mean scores of health status of both groups showed no statistical significances at the .05 level, with the mean scores of health status of the experimental group tended to be higher than that of control group; 3) The mean scores of self-health care concerning practices of the experimental group before and after the experiment showed no statistical significances at the .05 level, but the mean scores in the experiment group obtained after the experiment were higher than that was obtained before the experiment a little bit which meant that thepre-retirement teachers had better health care; 4) The mean scores of self-health care concerning practices of both group showed no statistical significances at the .05 level, but the mean scores of the experimental group were higher than the control group; 5) The experiment group who participated in self-health care model in the developed self-health care model showed a very good level.